Kualitas Perairan Situ Gintung, Tangerang Selatan - Saiful Bahri; Firdaus Ramadhan; Indhina Reihannisa (Biogenesis: Jurnal Ilmiah Biologi, 2015)
Situ Gintung is lake located in East Ciputat regional, South Tangerang City. Various activity of human such as building residence, floating net cages, fishing and disposal waste from buildings around lake had changed aquatic function in Situ Gintung that arriving allegedly decreased and not compatible with government regulation RI number 82 year 2001 on water quality management and water pollution control. The aimed of this research is perceiving water quality of Situ Gintung based on physical, chemical, and microbiological aquatic as well as find pathogenic bacteria in Situ Gintung aquatic. Parameters of physical chemistry which were measured was the degree of acidity (pH), dissolved oxygen (DO), five day biochemical oxygen demand (BOD5), total dissolved solids (TDS) using Water Quality Checker (WQC) while metal components parameter was Fe and Cu usingAtomic Absorption Spectrofotometre (AAS). Microbiology test form was total colliform with Most Probable Number (MPN) and biochemistry for pathogen bacteria. The temperature parameter, content of DO and are below the quality standard, while parameters such as BOD5 and pH is in the quality ofthe raw differences 3.11 to 6.49 mg / l and 4 to 6.51. Total collifom bacteria value in every station is outside air quality standard class one, > 1100 cell/100 ml. Based on Physical, Chemical and Microbiological water Situ Gintung no longer corresponded to water class one PP number 82 year 2001 and there are seven strains of Salmonella sp. bacteria in every station except Station 6.Keywords: aquatic quality, Coliform bacteria, pathogenic bacteria, Situ Gintung, water standard